Política pública de saúde : uma abordagem sobre o acesso dos usuários à atenção primária na zona rural do município de Monsenhor Hipólito/PI - Costa, Edinara Fernanda de Jesus (2021)
The primary health care policy concerns health promotion, protection and recovery services, considered the gateway to the Brazilian health system. In view of this, the research in question has as its main objective to analyze the potential and challenges, structural, situational and the perception of users, regarding the effective access of the population to Basic Health Units in the rural area of the municipality of Monsenhor Hipólito/PI, to implement the principle of universality advocated by the SUS. The universe of this research included users of basic health units in the rural area of Monsenhor Hipólito/PI, and access to the sample of this study, which comprises a total of 75 users of health units, was through the application of a questionnaire with the users of such units. The theoretical-methodological contribution of historical-dialectical materialism was used, which apprehends the complexity of social reality in its multiple determinations from a perspective of totality. According to identified data, it was noticed that the municipality is mostly composed of rural workers who survive from agriculture and livestock. Based on the National Register of Health Households (2019), the municipality has 7 primary health care establishments managed by the municipal administration, 5 of which are located in the extension of the rural area. Even so, the distance between health units and users' homes is the first difficulty faced by users in accessing the health services of the primary care network in the city, but it is not the most highlighted by the subjects of this research. In addition to the distance, the greatest difficulties faced by users in accessing primary health services is the lack of daily availability of basic services at health units, especially the lack of medical professionals. Therefore, it is understood that the rural population finds it difficult not only to travel to the nearest health unit, but also to have access to the provision of basic services, which are not available every day of the week.